Ostatni Żyd w Europie. Pieśń o zamordowanym żydowskim narodzie J. Kacenelsona - Pawelec, Andrzej; Sitarz, Magdalena (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
Itzhak Katzenelson was a Polish Jew who survived the uprising in the Warsaw Ghetto, to be murdered a year later in Auschwitz. During his internment inVittel, he wrote a requiem for the European Jewry. The paper offers a preliminary analysisof the text and asks the question: what is involved in the feeling that one is the last of a people?